Understanding Safety Performance among Medical Laboratory Staff - Siti Faisyah, Jaafar (2010)
The study was conducted to investigate the affections of five facets of Work Safety Scale (WSS) on compliance safety behaviour and what can these safety perception measurements contribute to the medical laboratory staff behaviours. This survey was done among 139 respondents in a teaching hospital in Kuala Lumpur by using the tool developed by Hayes et al (1998) that measured the safety perceptions of job safety, co-worker safety, supervisor safety, management safety and satisfaction of safety programme towards compliance safety behaviour. All the results of measurement were then being analysed statistically with descriptive frequencies on demography, reliability tests on internal consistency, correlations and regressions analysis. The findings indicated that the most significant facets were co-worker safety, job safety and satisfaction on safety programme that might contributed towards safety behaviour. Supervisory safety was the rejected facet in the perception measurements as it depicted in negative significant results. These results could be related to the demographic measurements upon age, job area and level of educations. Further suggestions were discussed according to the findings to complete the conclusions and recommendations.